2013
DOI: 10.3389/fnins.2013.00058
|View full text |Cite
|
Sign up to set email alerts
|

The Nav1.9 channel regulates colonic motility in mice

Abstract: The colonic migrating motor complex (CMMC) is a major pattern of motility that is entirely generated and organized by the enteric nervous system. We have previously demonstrated that the Nav1.9 channel underlies a tetrodotoxin-resistant sodium current which modulates the excitability of enteric neurons. The aim of this study was to observe the effect of loss of the Nav1.9 channel in enteric neurons on mouse colonic motility in vitro. The mechanical activity of the circular muscle was simultaneously recorded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 64 publications
(139 reference statements)
8
26
0
Order By: Relevance
“…Although the major consequence of the SCN11A mutation is diminished pain sensation, chronic diarrhea is common, and Na v 1.9 is expressed in myenteric neurons. (45,46) Na v 1.9 knockout mice have significantly increased intestinal motility, documenting that Na v 1.9 functions in colonic motor activity, (47) and perhaps explaining our patients' chronic diarrhea. Hyperhidrosis in the daughter too might represent autonomic dysfunction.…”
Section: V) Discussionsupporting
confidence: 53%
“…Although the major consequence of the SCN11A mutation is diminished pain sensation, chronic diarrhea is common, and Na v 1.9 is expressed in myenteric neurons. (45,46) Na v 1.9 knockout mice have significantly increased intestinal motility, documenting that Na v 1.9 functions in colonic motor activity, (47) and perhaps explaining our patients' chronic diarrhea. Hyperhidrosis in the daughter too might represent autonomic dysfunction.…”
Section: V) Discussionsupporting
confidence: 53%
“…Therefore the phenotype is mainly caused by nerve dysfunction and not by its absence. The p.L811P variant causes a complex pattern of effects on neuronal subtype activity: it is excitatory in the enteric plexus (Na V 1.9 knockout mice have increased intestinal activity 5 ), in sweat glands leading to hyperhidrosis and in ano-rectal nociceptors showing these innervations are functioning; but it is inhibitory in most nociceptors and in infective inflammation (which also occur in sensory neuropathies where small unmyelinated nerves are absent). The Na V 1.9-CIP phenotype is unique and clearly clinically distinguishable from Na V 1.7-CIP, which is accompanied by anosmia but not gastrointestinal motility disturbances or muscle weakness.…”
mentioning
confidence: 99%
“…2 In this light, epidermal thickening in GJB2 carriers 3,4 has been proposed as a possible advantage reducing infections and bacterial invasion through skin. 5,6 Moreover, in vitro functional studies demonstrated that the loss-of-functional GJB2 expression provides improved protection against gastrointestinal bacterial pathogens. 7 In particular, enteropathogenic Escherichia coli and Shigella flexneri may induce a strong selective effect, being the most common causes of diarrhoea.…”
mentioning
confidence: 99%
“…Prominent hyperhidrosis and gastrointestinal malfunction in the affected individuals may be a consequence of autonomic dysfunction. Na v 1.9 is indeed expressed in pacemaker neurons of the intestinal tract of rodents, and Scn11a knockout mice display altered colonic motility [35][36][37] .…”
Section: Scn11amentioning
confidence: 99%